Experimental investigation on dynamic behavior of silt-rich fly ash using cyclic triaxial and bender element tests - Ram A.K.; Mohanty S. (My University, 2025)
The present study mainly focuses on the evaluation of dynamic properties of silt-rich fly ash from Renukoot, India, under large and small strain conditions using cyclic triaxial and bender element test, respectively. The influence of confining pressure, loading frequency, relative compaction, and shear strain amplitude on dynamic properties of fly ash under small strain and large strain condition has also been studied. The dynamic shear modulus (G) found experimentally from cyclic triaxial test shows the decay in a nonlinear manner with the increment of loading frequency and cyclic shear strain. The increment in dynamic shear modulus of fly ash was noticed with the increment of relative compaction and confining pressure. Similarly, the increase in small strain shear modulus (Gmax) was observed with the increment of confining pressure, relative compaction, and frequency of the waveform. The decrease in damping ratio was observed with an increase in shear strain, especially for higher strain side (i.e., γ > 0.5%) but vice versa is not true for lower strain side (γ < 0.5%). Therefore, irrespective of the soil type, there exists a threshold strain beyond which damping ratio decreases with an increase in shear strain. All the parameters except loading frequency have a prominent impact on G and Gmax is sensitive to the entire considered factors. Finally, empirical correlations were developed between normalized shear modulus ratio (G/Gmax) and damping ratio (D) of silt-rich fly ash with cyclic shear strain (γ) at different confining pressure, relative compaction, and loading frequency. The developed correlations can be helpful in calculating the dynamic properties of Renukoot fly ash at different strain levels. The developed correlations will also assist in the safe design of structures with fly ash as geo-material in the seismic-prone regions. © 2021, Springer Nature Switzerland AG.